Impact of asthma, exposure period, and filters on human responses during exposures to ozone and its initiated chemistry products - Fadeyi, M. O. (2014)
The impact of asthma, exposure period, and filter condition downstream of the mixing box of air-conditioning system on building occupants' perceptual response, work performance, and salivary α-amylase secretion during exposures to ozone and its initiated chemistry products is studied. The experiments were conducted in a field environmental chamber (FEC) (240 m3) simulating an office environment. Experiments were conducted during periods when the air-handling system operated with new or used pleated panel filters at constant recirculation (7/h) and ventilation (1/h) rates. Average ozone and secondary organic aerosols (ozone-initiated chemistry products) measured during non-asthmatic and asthmatic subjects' 3-h exposures in the FEC were in the ranges approximately 20–37 ppb and approximately 1.6–3 μg/m3, respectively. Asthmatic subjects' perceived odor intensity and sensory (eye, nose, and throat) irritation ratings were generally lower than those of non-asthmatic subjects, possibly explaining why asthmatic subjects accept perceived air quality more than non-asthmatic subjects. However, asthmatic subjects' perceived physiological-like symptom ratings (flu, chest tightness, and headache) and concentrations of secreted salivary α-amylase were generally higher than those of non-asthmatic subjects. Asthmatic subjects had significantly lower accuracy than non-asthmatic subjects in a task that required higher concentration although they had higher work speed. Filter condition did not make any significant difference for subjects' responses.